Potential anti-inflammatory activity of low molecular weight heparin in patients with exacerbations of COPD – short report - Rybacka-Chabros, Barabara; Pietrzak, Aldona; Chabros, Paweł; Milanowski, Janusz (Polish Journal of Public Health, 2014)
Introduction. Anti-inflammatory, separate from anti-thrombotic activity of low molecular weight heparin, is still not well documented.Aim. We estimated the influence of enoxaparin on serum levels of tumor necrosis factor alpha, as the pro-inflammatory cytokine, and interleukin-12, as the heparin-binding, anti-inflammatory cytokine, in patients with exacerbations of chronic obstructive pulmonary disease.Material and methods. Seventy-three consecutive patients (48 males, 25 females) aged 56-75 years without thromboembolic history, were enrolled into the study. They were randomized to group who received enoxaparin in one daily dose 40 mg, or to group who did not receive it. Patients receiving oral anti-coagulants were excluded from the study. Using ELISA approach, we evaluated serum levels of tumor necrosis factor-alpha and interleukin-12 at the following periods: before the first dose of enoxaparin, after 7 days of treatment and 14 days of treatment. Serum level of the C-reactive protein was evaluated simultaneously.Results. In enoxaparin recipients statistically significant (p